Implementasi Perencanaan Strategis Organisasi dalam Rangka Pencapaian Tujuan Pendidikan - Elvi, Syoviana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
Strategic planning in some areas of executive education is often not a serious concern of education managers. Strategic planning is only done on one of the administrative requirements without being used to guide education providers. Organizations are driven solely by intuition and leadership experience. Moreover, strategic plans have not been prepared based on thorough organizational analysis in manufacturing. The achievement of organizational goals effectively and efficiently can only be done in solid strategic planning. The preparation of strategic plans can make considering the internal and external environment of the organization, strategy formulation, strategy implementation and strategy evaluation. Optimizing the role of strategic planning can be done by increasing the commitment of organizational members and the proper use of transformational leadership